Altered white matter microstructural integrity in patients with postherpetic neuralgia: a combined DTI and DTI-NODDI study - Qian, Wei; Xu, Xiaopei; Wu, Ying; Yu, Lina; Wang, Chao; Yan, Min; Yu, Risheng (Frontiers in Neuroscience, 2025)
BackgroundPostherpetic neuralgia (PHN) is a debilitating condition resulting from herpes zoster infection, characterized by persistent pain that significantly impacts quality of life. This study aimed to investigate the white matter microstructural alterations associated with PHN and to assess the relationship between diffusion metrics and clinical symptoms.MethodsA total of 29 patients with PHN, 28 patients recovering from herpes zoster (RHZ), and 27 healthy controls (HC) were recruited, and clinical assessments were obtained to evaluate pain intensity and psychological distress. Diffusion tensor imaging (DTI) data was collected, followed by analysis of diffusion and neurite orientation dispersion and density imaging (NODDI) metrics. Statistical analyses included ANOVA to compare groups and Pearson correlation coefficients to assess relationships between imaging metrics and clinical outcomes.ResultsPHN patients exhibited significantly altered white matter integrity, specifically in neurite density index (NDI) and orientation dispersion index, compared to both RHZ patients and HC. Significant correlations were also found between altered imaging metrics and clinical assessments of pain and emotional distress, with lower fractional anisotropy (FA) and NDI associated with higher pain scores and psychological symptoms.ConclusionOur study highlights significant microstructural changes in white matter tracts in patients with PHN, indicating compromised neural integrity that correlates with increased pain perception and emotional distress. NODDI demonstrated superior sensitivity in detecting these alterations compared to traditional DTI metrics, underscoring its potential for enhancing diagnostic and therapeutic approaches in managing chronic pain conditions like PHN.